2018
DOI: 10.1186/s13017-018-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative management of appendiceal phlegmon or abscess in children less than 3 years of age

Abstract: BackgroundIn children less than 3 years of age, there is little experience in the nonoperative management of appendiceal phlegmon or abscess (APA), especially in APA with an appendicolith. The purposes of this study were to evaluate the effects of an appendicolith and the success rate of nonoperative management for APA in these young children.MethodsChildren younger than 3 years of age with APA who underwent attempted initial nonoperative treatment between January 2008 and December 2016 were reviewed. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Our study agreed with previous studies that percutaneous drainage resulted in good treatment outcome ranged from 78.6% to 100%. [5][6][7][8] A meta-analysis by Anderson and Petzold 9 found that antibiotics treatment alone for periappendiceal abscess had a successful outcome in 93% of the cases, and percutaneous drainage was needed for only 20%. Furthermore, a study by Miftaroski et al 11 found only Original Article SMJ 1 out of 15 patients (7%) who had initially successful treatment via combining antibiotics and CT-guided drainage for a perityphlitic appendiceal abscess had recurrent appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study agreed with previous studies that percutaneous drainage resulted in good treatment outcome ranged from 78.6% to 100%. [5][6][7][8] A meta-analysis by Anderson and Petzold 9 found that antibiotics treatment alone for periappendiceal abscess had a successful outcome in 93% of the cases, and percutaneous drainage was needed for only 20%. Furthermore, a study by Miftaroski et al 11 found only Original Article SMJ 1 out of 15 patients (7%) who had initially successful treatment via combining antibiotics and CT-guided drainage for a perityphlitic appendiceal abscess had recurrent appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous drainage with intravenous (IV) antibiotics in periappendiceal abscess is an effective and minimally invasive treatment. [4][5][6][7][8][9] However, some patients develop complications after percutaneous drainage leading to prolonged hospitalization or emergency appendectomy. An algorithm for the management of periappendiceal abscesses indicated that, if there is diffuse peritonitis, the patient should undergo immediate surgery.…”
Section: Original Article Smjmentioning
confidence: 99%
“…2,19 and are using it in the next combination: 'phlegmon of floor of the mouth' , 'phlegmon of the submandibular area' , 'phlegmon of the neck' , etc. The authors from the rest of the world are widely using the term 'phlegmon' in head neck, thoracic, abdominal surgery, and orthopaedics in the next combinations: 'retropharyngeal phlegmon 20,21 ' , 'phlegmonous esophagogastritis 22 ' , 'abdominal phlegmon 23 ' , 'appendicial phlegmon 24 ' , 'phlegmon of the hand 25 , 26 ' , 'phlegmon of the digital flexor tendon sheaths 27 ' , etc.…”
Section: Discussionmentioning
confidence: 99%
“…Отже, великого значення в комплексній діагностиці ГА набуває зйомка, реєстрація та обробка всього комплексу отриманих лабораторно-інструментальних показників, що відображають рівень ЕІ в режимі реального часу. При цьому важливість динамічних мультидисциплінарних підходів до діагностики ГА в дитячому віці сьогодні продиктована і тим, що у спеціальній літературі широко дискутується можливість проведення консервативного / відтермінованого лікування патології, у тому числі при апендиколіті в дітей віком до 3 років [21].…”
unclassified